ANALISIS RISIKO PELAKSANAAN PROYEK PEMBANGUNAN PRASARANA PENGENDALI BANJIR TUKAD SUNGI YANG BERPENGARUH TERHADAP KINERJA BIAYA DAN WAKTU - Ni Putu Indah Yuliana; Ni Made Sintya Rani (Fakultas Teknik, Universitas Wiraraja, 2020)
Sungi’s river flood control infrastructure development project has a high enough risk. The research objective is to identify, assess, and respond to the risks that affect the cost and time performance of the project. The study was conducted by a mixture of quantitative descriptive and qualitative descriptive methods. Data collection by interview and data analysis by Severity Index (SI). The results showed that the identified risks were 25 (twenty-five) risks from 8 (eight) sources of risk. Risks that have extreme value and affect cost performance are addendums when carrying out work, changing or erratic weather that hinders work and adjustments to field conditions resulting in work design changes. Risks that have extreme values ​​and affect the performance of time are a lack of funding to carry out work and an error in field measurements to determine the point of work so it does not match the picture. The response to risks includes service providers providing initial funding, implementing addendums immediately, using weather forecast data from the BMKG, re-measuring, and making changes immediately, and asking for the approval of the work owner.